Exploring the intricate cross-talk between clonal expansion and the bone marrow niche - Ngo, Steven; Papazoglou, Despoina; Huerga Encabo, Hector; Bonnet, Dominique (Frontiers in Hematology, 2024)
Haematopoietic stem cells (HSCs) reside within an intricate network of cells in the bone marrow (BM) niche. HSC crosstalk with niche compartments influences lineage determination and blood cell production, while independent niche interactions are essential for the maintenance of HSC quiescence. How different niche components influence the genetic diversity of HSCs represents an expanding field of investigation. As such, we will summarize the current knowledge of the contribution to the Darwinian evolution of mutant HSCs of both haematopoietic cells and non-haematopoietic cells residing in the BM. In this review, we will disentangle how somatic evolution associates with the niche at two stages: from (1) the stage of preleukaemic HSC expansion and clonal haematopoiesis (CH) to (2) leukaemia-initiating cells (LICs) and the development of myeloid malignancies, with acute myeloid leukaemia (AML) being the most prevalent. We will finally describe current challenges such as limitations in models used in the field or the difficulty in studying specific genetic clones in isolation.